Application of Least-Squares Method to Time Series Analysis for 4DPM Matrix - Dong, Mingwang; Huang, Linfu; Wu, Xueqin; Zeng, Qingguang (IOP conference series. Earth and environmental science, 2020)
In the past 10 years, considerable attention has been paid to PMBOKM, and it has combined with specific examples. However, quantitative methods are rarely used for analysis. We select Han River Estuary Waterway Engineering Project as a study case. Based on the relationship between the stages of the project management system, it tries to analyse the first five stages of matrix time series of 4DPM in the three major forms by the least squares method, and the method is divided into four steps to solve the matrix. In addition, the matrix is subject to function changes and transpose processing, and then solved by the least squares method too. According to the set solution method, the matrix can be solved, and eight cases can be obtained. By comparing the errors, under the condition of transposed matrix, the function of the most suitable for matrix transmission can be found. So, it is known that the method is feasible and effective in 4DPM model matrix analysis.